'We were here – Three persons' journeys of life'. Issue 1 (1st June 2011) - Laidlaw, R
Abstract : Narrative interviewing can be traced in American history as far back as 1920. Its application to Advance Care Planning (ACP) as a research method has yet to be extensively researched but where explored, it is the meaning portrayed and the perspective of the value of the event that assists learning. The methodology being less structured and using conversational interaction provides ACP Facilitators' opportunity to reflect on elements such as culture diversity and aspects of life that have compelling interest. My curiosity in narrative interviewing began in the 80s when involved in death and dying education and was regenerated when implementing the Respecting Patient Choices Program (RPC) at Ipswich Hospital and the surrounding West Moreton Health Service District in 2009. Through the RPC processes including, training of Facilitators and leading the facilitation of ACP conversations in acute, residential and community settings it contributed to my desire to scribe the experiences and lives of three special people and follow their stories through to death with family members. Scribing these privileged moments in time has provided me with invaluable lessons in life and living, consolidated my reasons of the importance of sharing their lives and their personal meanings when training and preparing Facilitators. The lives explored in context confront positively the importance of ACP and become the infancy of a library of 'real experiences' that can be intertwined in models of ACP learning.